Hypothetical Interventions for Falls Among Older Adults: An Application of the Parametric G-Formula - Ren, Jiaojiao; Li, Guangyou; Zhang, Liju; Zhang, Na; Ren, Juan (Frontiers in Medicine, 2021)
Introduction: Falls, which have a higher incidence and mortality due to accidental injuries, are a major global health challenge. The effects of lifestyle factor, health indicator, psychological condition, and functional status interventions on the risk of falls are unknown and the conventional regression model would not adjust for the confounders. This study aimed to evaluate the 4-year risk of falls on the basis of these hypothetical interventions among Chinese older adults. Methods: Data were obtained from 9 692 aged 65 years and over older adults in the China Health and Retirement Longitudinal Study wave, from 2011 to 2015. We used the parametric g-formula to evaluate the risk of falls on the basis of independent hypothetical interventions of sleep duration, social activities, smoking status, drinking status, body mass index (BMI), systolic blood pressure (SBP), vision, depression, activities of daily living (ADL), and their different joint intervention combinations. Results: During the follow-up of 4 years, we documented 1 569 falls. The observed risk of falls was 23.58%. The risk ratios (95% confidence intervals [CIs]) of falls under the intensive hypothetical interventions on increasing sleep duration, participating in more social activities, quit smoking and drinking, reducing BMI and SBP, better vision, alleviating depressive symptoms, and improving ADL capability were 0.93 (0.87-0.96), 0.88 (0.79-0.92), 0.98 (0.95-1.03), 0.97 (0.95-1.02), 0.92 (0.86-1.03), 0.93 (0.87-1.04), 0.86 (0.74-0.91), 0.91 (0.85-0.96), and 0.79 (0.74-0.85), respectively. The feasible and intensive joint hypothetical intervention reduced the 4-year fall risk by 22% (95% CI: 0.52-0.91) and 33% (95% CI: 0.56-0.72), respectively. Conclusions: Hypothetical interventions for increasing sleep duration, participating in more social activities, better vision, alleviating depressive symptoms, and improving ADL capability help protect older adults from falls. Our findings suggest that a combination of lifestyle factors, health indicators, psychological conditions, and functional status may prove to be an effective strategy for preventing falls among older adults.